(untitled) (Physical Education, Health and Social Sciences, 2025)
In the context of intricate projects, Project Management Systems (PMS) have become widely used in project-based organizations as they are increasingly depending on digital versions of their systems to improve their planning, coordination and monitoring processes as well as decision-making. Although it has been widely adopted, there is still inconsistency in empirical evidence on the effectiveness of PMS in enhancing project management efficiency. Delays in schedule, cost overruns, and loss of coordination are still witnessed in many organizations despite the adoption of technologically advanced project management platforms. These discrepancies demonstrate the necessity to look into the organizational circumstances in which the PMS lead to the efficiency results. Based on a socio-technical approach, the paper explores the connection between Project Management Systems and project management efficiency coupled with the mediating effect of organizational culture. This study will combine DeLone and McLean model of Information Systems Success with the Denison model of Organizational Culture to determine how the combination of technological capabilities and cultural conditions determine project management efficiency. Quantitative cross-sectional research design was used and the researcher collected data of professionals operating in project-based organizations in various sectors in Pakistan such as construction, information technology, engineering, and services. The hypothesized relationships between PMS and organizational culture and project management efficiency were tested using structural equation modeling (SEM). The results show that the Project Management Systems have a great influence on the efficiency of project management as it enhances the accuracy of planning, effectiveness of monitoring, and coordination among the stakeholders of the project. The findings also prove that PMS can have a beneficial effect on organizational culture due to their ability to foster transparency, accountability, and cooperative work practices. It also turned out that organizational culture has a positive impact on the efficiency of project management as well. Notably, mediation analysis shows that the correlation between PMS and efficiency is partially mediated by organizational culture, indicating that technological systems are the main contributory to performance results when they exist in friendly cultural contexts. These discoveries can be used in the literature because they present a combined socio-technical account on project management efficiency and also because they give an empirical report within the context of developing economies. The research has its practical implications in the organizations that aim to reconcile the digital project management system with the organizational culture to attain sustainable enhancement of the project performance.